A PEEP INTO THE FUTURE THROUGH THE PAST: A BIBLIOMETRIC ANALYSIS ON WOMEN TRAVELERS - Dr. Gagandeep Soni; Sarah Hussain; Shekhar; Dr. Rachna Chandan (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2024)
The research explores the progress of studies on women travelers, examining publication trends, top contributors, collaborations, and thematic areas, while also exploring ways to make travel more convenient. For the achievement of these research questions, a bibliometric analysis has been conducted using data from the articles published in 41 journals dating from 1982 to 2023. For bibliometric analysis, collected data was analyzed with descriptive analysis, science mapping as bibliographic coupling, citation metrics, prestige analysis, keyword co-occurrence metrics; and network analysis as co-author analysis and co-citation analysis. The study reveals the top ten authors, organizations, and countries in women traveler-related literature, but a low total publication count suggests the need for comprehensive research. Five major themes that emerged were Women Travelers and Solo Travel, Women Travelers and Travel Motivation, Women Travelers and Purchase Intention, Women Travelers and Girlfriend Getaways, and Women Travelers, and Sexual Behaviour. The study identifies research gaps for future studies and suggests managerial actions to make women's travel more convenient. The study's values lie in enhancing the understanding of women traveler research, raising awareness of research frontiers, and guiding future directions in business travel niche market segments.